Methods of Teaching Literary Texts at Sekolah Tinggi Ilmu Bahasa Arab Ar-Rayah Sukabumi: منهج تدريس النصوص الأدبية في جامعة الراية بسوكابومي - Mulyadi, Mulyadi; Bakri Muhammad Bakheit (Institut Muslim Cendekia, 2025)
Literary texts are good literary heritage, both ancient and modern, poetry and prose, as well as materials through which students' linguistic, intellectual and expressive skills are developed. This research aims to determine the approach to teaching literary texts at STIBA Ar Raayah, because teaching literary texts has a big role in forming students' skills, expanding their knowledge, perfecting their language skills, encouraging them to increase their literary level, and increasing their expression. The approach taken by the researcher is an analytical description approach, and this researcher uses a documentation method to collect data, namely the documentation method, which is one method of collecting data in various ways by displaying or analyzing existing documents created by the researcher. subject yourself or someone else. The results of the research are as follows: Literary texts are: eloquent and constructive speech intended to influence the emotions of readers and listeners, whether in the form of poetry or prose. includes sermon texts, including Arabic proverbs, Arabic rules, etc., as well as curriculum. Teaching texts are based on curriculum elements, namely: objectives, content, teaching methods, and then evaluation.